"By stages towards what we mean to say:" diegetic rupture as a tool of devotion. Issue 3 (2nd July 2020) - Decker, John R.
Abstract: The article discusses the use of troubled temporalities and metaleptic prompts as mechanisms designed to help support devotional acts with religious images. Late medieval and early modern contemplation routinely involved various mental operations that relied on atemporal and asynchronous approaches to narrative. As a result, the votary was often required to engage in acts of complex mnemonic chaining and contemplative expansion as she or he performed devotion. The article concludes the analysis by asserting that associations derived from this process were not completely open but, instead, were conditioned by framing devices that pointed the faithful toward higher-level concepts useful for salvation.